Comparison of rheological properties of graphene / carbon nanotube hydrogenated oil based biodegradable drilling fluid - Chai, Y.H. (Institute of Physics Publishing, 2017)
An experimental investigation has been carried out to investigate the rheological properties of graphene / carbon nanotube hydrogenated oil based biodegradable drilling fluid at different nanoparticle loadings. The rheological behaviours of interest in this investigation are the viscosity and shear stresses of two different nanofluids respectively. The limiting parameters in this study are 25 ppm, 50 ppm and 100 ppm weight concentration at operating temperature ranging from 30°C to 50°C. Both nanofluids are subjected to shear rate ranging from 0 - 140 s-1 for comparison of rheological behaviours. Both samples' viscosity reduces to base fluid's viscosity value at higher shear rate with carbon nanotube-hydrogenated oil yielding higher viscosity compared to graphene-hydrogenated oil for all nanoparticle loadings at lower shear rate. Shear stress analysis also shows similar results with carbon nanotube based samples showing higher stress between the two at all particle loadings. Both samples show Newtonian behaviour that is similar to base fluid even at higher particle loadings. Analysis revealed both nanofluids yields close to zero yield stress even with the presence of graphene or carbon nanotube particles. The significance of this study shows that addition of low nanomaterials for enhancement of drilling fluids can improve its thermophysical properties without compromising the quality of drilling fluids such as viscosity and shear stress properties. © Published under licence by IOP Publishing Ltd.